Deciphering why petrol stations have become hot spots for crime in South Africa - Nyahunda, Louis; Rakubu, Kholofelo Anna (Edelweiss Applied Science and Technology, 2024)
In the ever-evolving landscape of criminal activity, petrol stations in South Africa have emerged as a prime target for malicious actors, capturing the attention of law enforcement agencies, researchers and various authorities. The rise in criminal activities at petrol stations in South Africa has become a mounting concern, with researchers and law enforcement agencies striving to understand the root causes and devise sustainable ways to curtail the scourge. This study explores the underlying factors that have contributed to the surge in criminal incidents at these perceived safe havens, delving into the empirical drivers of this alarming trend. The study employed a qualitative research approach which operated within the exploratory research design. A purposive sampling technique was utilised to select 10 petrol stations around Gauteng province. In this view, petrol attendants, petrol station owners and members of the security patrols participated in the study. A total of 30 participants gave their insights to the study. The findings revealed that petrol stations have become hunting grounds because of the availability of an assortment of items. Furthermore, the study established that the flourishing of crime syndicates, the environmental design of most petrol stations, limited to no periodic police patrols and outdated security systems are contributing factors to this conundrum. This paper posits that the transformation of petrol stations into preferred hunting grounds for criminals in South Africa is a multifaceted phenomenon, shaped by the interplay of a lack of technological advancements to combat crime, pitfalls in the broader security landscape in the country and lack of pragmatism in implementing the Crime Prevention through Environmental Design strategy.